Strategi Pengembangan Pelabuhan Sunda Kelapa Sebagai Gerbang Wisata Sejarah Di Jakarta - Novi Handayani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research was conducted with the aim to see the potential of Sunda Kelapa Port through the resources possessed by the theory of Resource Based View (RBV) and then look for strategies that can be used to develop historical tourism in the Sunda Kelapa Port. The informant and respondent of this research is PIC acceleration of the old city area of the Ministry of Tourism, PT Pelindo II, Tour Guide, and tourists. Data collected by observation, interview, literature study and questioner. This research used qualitative descriptive method in order to analyze the data that have been collected by using IFE and EFE matrix, IE Matrix, SWOT Matrix and QSPM matrix. Based on the analysis and discussion that has been described, the product development strategy is the main strategy that must be developed by Sunda Kelapa Port to be able to compete with other tourist destinations.